The 355 [videorecording (Blu-Ray + DVD)] - Kinberg, Simon; Rebeck, Theresa; Chastain, Jessica, 1977-; Cruz, Penélope; Fan, Bingbing, 1981-; Kruger, Diane, 1976-; Nyong'o, Lupita; Ramírez, Édgar, 1977-; Stan, Sebastian, 1982- (Universal, 2022)
CIA agent Mason 'Mace' Brown joins forces with a rival German agent, a cutting-edge computer specialist and a Colombian psychologist when a top-secret weapon falls into the hands of a group of mercenaries. Together, the four women embark on a breakneck mission to save the world while staying one step ahead of a mysterious figure who's tracking their every move.